Undamped non-linear vibration mechanism of bolted flange joint under transverse load. Issue 3 (4th May 2023) - He, Liange; Li, Tianhua
ABSTRACT: Bolted flange joints are commonly utilized in engineering constructions; nevertheless, their dynamic behavior is complicated when nonlinearity is present. The bolted flange joint structure in this research is considered as a spring-mass system, and the equivalent axial two bi-linear springs-bending beam model, as well as the system's vibration control equation, is created to examine the joint structure's vibration characteristics under transverse stress. The results indicate that when the spring stiffness is constant and the stiffness is a linear function of displacement, and the mass matrix of the vibration control equation is coupled, the system produces only transverse vibration upon transverse impact; when the spring axial stiffness is a linear function of displacement and the mass matrix of the vibration control equation is not coupled, the spring stiffness is bilinear and the stiffness is a quadratic function of displacement, the system will vibrate transversely and longitudinally under the transverse impact. Regardless of how the spring stiffness is simplified, the system's transverse or transverse and axial movement is a stable periodic vibration with a vibration response proportional to the system's mass and the radius L of the connected cylindrical shell.